2000
DOI: 10.1590/s0101-81752000000400004
|View full text |Cite
|
Sign up to set email alerts
|

Distributional patterns and possible origins of the tribes and genera of Coelidiinae (Homoptera, Membracoidea, Cicadellidae)

Abstract: Leafhoppers are well known biological indicators of zoogeographical regions owing, in part, to their phytodependency, high host plant specificity and relatively low vagility. In this connection, we discuss distributional patterns and possible zoogeographical origins of nine constituent tribes and their genera of the pantropical subfamily Coelidiinae. Among 118 known genera, only eight currently occupy more than one zoogeographical region, indicating an extremely high endemic profile which supports the proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Leafhoppers are excellent biological indicators of zoogeographical regions and prime models for biogeography studies due to their high generic endemism (Nielson & Knight, ). Only a few prior studies have used their distribution to focus on the historical biogeography at a higher taxon to explore the origin of the group (Nielson & Knight, ; Nielson et al ., ; Yuan et al ., ). However, the patterns of diversity and distribution related to ecological biogeography, on a broad scale, are still unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Leafhoppers are excellent biological indicators of zoogeographical regions and prime models for biogeography studies due to their high generic endemism (Nielson & Knight, ). Only a few prior studies have used their distribution to focus on the historical biogeography at a higher taxon to explore the origin of the group (Nielson & Knight, ; Nielson et al ., ; Yuan et al ., ). However, the patterns of diversity and distribution related to ecological biogeography, on a broad scale, are still unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Concerning the Cicadellidae, Nielson & Knight (2000) and Nielson et al . (2000) suggested that the Proto‐Antilles movement isolated ancestors of extant genera of the Cicadellinae, Coelidiinae, and Agalliinae.…”
Section: Discussionmentioning
confidence: 97%
“…Several Auchenorrhyncha families have genera with endemic representatives in the Antilles (Ramos, 1988; Nielson & Knight, 2000; Nielson, Knight & Zhang, 2000). About 81% of the Cicadellinae species occurring in the Greater Antilles are endemic (Ramos, 1988).…”
Section: Discussionmentioning
confidence: 99%